Vascular expression driven by the promoter of a gene encoding a high-affinity potassium transporter HAK5 from Eucalyptus grandis - Costa, Carolina S. [UNESP]; Bravo, Juliana P. [UNESP]; Ribeiro, Cíntia L. [UNESP]; Soprano, Adriana S. [UNESP]; Sassaki, Flávio T. [UNESP]; Maia, Ivan G. [UNESP] (Springer Nature, 2017)
The construction of expression cassettes harboring tissue-specific promoters is a viable alternative to limit transgene expression to specific organs and cell types. In this study, we have functionally characterized the promoter of a Eucalyptus grandis gene encoding a putative high-affinity HAK5-like potassium (K+) transporter (designated EgHAK5) showing root-specific expression. The ability of the EgHAK 5′-flanking region (~1.3 kb) to drive root-specific expression of a reporter gene (β-glucuronidase; GUS) was examined using transgenic tobacco plants. Histochemical analysis revealed enhanced GUS staining in the vasculature of leaves, hypocotyls and roots, which was also confirmed in histological cross-sections. Moreover, the relative expression of GUS in the roots of the generated transgenic lines was increased in response to K+ starvation. Overall, our results indicate that, in a heterologous system, the EgHAK5 promoter shows expression in vascular tissues, mainly within the phloem, and is up-regulated upon potassium deprivation.
Keywords: Eucalyptus; Potassium transporter; Promoter; Root; Vascular expression